Anticipating the "Silver Tsunami": Prevalence Trajectories and Comorbidity Burden among Older Cancer Survivors in the United States - Bluethmann, Shirley M; Mariotto, Angela B; Rowland, Julia H (Cancer epidemiology, biomarkers & prevention, 2016)
Cancer survivors are a growing population, due in large part to the aging of the baby boomer generation and the related "silver tsunami" facing the U.S. health care system. Understanding the impact of a graying nation on cancer prevalence and comorbidity burden is critical in informing efforts to design and implement quality cancer care for this population. Incidence and survival data from 1975 to 2011 were obtained from the Surveillance, Epidemiology, and End Results (SEER) Program to estimate current cancer prevalence. SEER-Medicare claims data were used to estimate comorbidity burden. Prevalence projections were made using U.S. Census Bureau data and the Prevalence Incidence Approach Model, assuming constant future incidence and survival trends but dynamic projections of the U.S. In 2016, there were an estimated 15.5 million cancer survivors living in the United States, 62% of whom were 65 years or older. The prevalent population is projected to grow to 26.1 million by 2040, and include 73% of survivors who are 65 years and older. Comorbidity burden was highest in the oldest survivors (those ≥85 years) and worst among lung cancer survivors. Older adults, who often present with complex health needs, now constitute the majority of cancer survivors and will continue to dominate the survivor population over the next 24 years. The oldest adults (i.e., those >75 years) should be priority populations in a pressing cancer control and prevention research agenda that includes expanding criteria for clinical trials to recruit more elderly participants and developing relevant supportive care interventions. Cancer Epidemiol Biomarkers Prev; 25(7); 1029-36. ©2016 AACR.